ANALISIS CORPORATE SOCIAL RESPONSIBILITY SEBELUM DAN SELAMA PANDEMI COVID-19 SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN PERTAMBANGAN DI INDONESIA - Tiara Rani Santoso (Applied Research in Management and Business, 2022)
The Indonesian government has designated the Corona Virus (Covid-19) outbreak as a national disaster in 2020 and is still ongoing until mid-2021. The pandemic has had a negative impact on the financial performance of companies that have been hit. On the other hand, the company is obliged to carry out corporate social responsibility (CSR) with poor financial performance conditions. Companies are faced with the decision to reduce the budget for csr implementation or implement CSR more actively to the community. The purpose of this study is to analyze the disclosure and ratio of CSR contributions before and during the Covid-19 pandemic and test the effect of disclosure and the ratio of CSR contributions to company value during the Covid-19 pandemic. The population in this study used companies permine listed on the Indonesia Stock Exchange in 2019 and 2020. The taking of sample used purposive sampling technique so that it was obtained by 13 companies as sample. The data analysis methods used are paired sample t-test and multiple regression. The results show that there is no difference in the disclosure and ratio of CSR contributions before and during the Covid-19 pandemic. This makes it clear that the company continues to carry out CSR even though its financial performance is not good. In addition, the disclosure and ratio of CSR contributions during the Covid-19 pandemic has no effect on the value of the company. This shows that investors do not pay much attention to csr activities carried out by the company during the Covid-19 pandemic. This research practically contributes to the literature by suggesting that companies continue to carry out CSR as a form of responsibility for the impact resulting from company operations to be able to help reduce social problems.